Eficiencia de dos técnicas de remoción de dentina cariada: químico mecánica con gel de papacarie® y de la técnica rotacional convencional en lesiones 1.2 en dentición decidua. - Aguirre Aguilar, Antonio Armando (2008)
PURPOSE: The aim of the study was to determine the efficiency in the removal of dentine decayed of chemomechanical caries removal with gel Papacarie® and with conventional mechanical method in injuries 1.2 in children´s primary teeth. METHODS: The experimental controlled clinical trial study with design of paired data, the sampled consisted of 30 primary teeth in 5-year-old children, distributed in 15 girls and 15 children who received a treatment of each one of the technologies proposed. The cavities were restored by Amalgam in case of the conventional mechanic method and with Ketac Molar in the chemomecanical method with gel Papacarie®. The efficiency in caries removal was judged on the basis of clinical criteria. Length of the time of removal of decayed dentine, total working time , managing of the pain in patient, better response of the behavior during the process and minor application cost. RESULTS: The results showed that Chemomechanical method with gel Papacarie® reduced the total working time, had more suitable managing of the pain, present a better behavior in the patient, and a minor cost of application. CONCLUSIONS: The chemomechanical method with gel Papacarie was more efficient in the majority of the studied variables.